DIAGNOSING THE NUTRITIONAL STATUS OF APPLE ORCHARDS AT SOUTH OF JORDAN - F Al-Nasir; K Al-Absi (Arab Universities Journal of Agricultural Sciences, 2005)
A test survey was conducted to determine the nutritional status of apple trees grown at four highly productive orchards in south of Jordan. Leaf and soil samples were taken from each orchard, and analyzed for the concentrations of macro- and micronutrients. Soils of Al-Shoubak tend to have high pH, low organic matter and high CaCO3 contents. The results showed that soil concentrations of N, K, Fe, Mn, Zn and Cu varied widely among the orchards. No deficiency or hunger signs of N, P, K, Mn and Zn nutrients were observed at any of the localities since concentrations of leaf nutrients were generally within the sufficient range, indicating adequate lev-els of fertilization applied to the trees. The leaf analysis has shown that Cu deficien-cy is found in some apple orchards. Soils and leaf nutrient levels were generally not well correlated with one another. The only highly significant correlation was be-tween soil P and leaf N. However, positive relations were observed among leaf P and Mn, Fe and Mn, Fe and Zn, and Mn and Zn contents.